Impact of DEM Resolution on Hydrological Simulation Accuracy of VIC Model - SHI Bin; REN Zheng; MENG Pengfei; JIA Tengfei (Renmin Zhujiang)
In order to research the impact of DEM resolution on hydrological simulation accuracy and operating efficiency of VIC model, this paper simulates the monthly runoff in the upper reaches of north source of Zhuozhang River through the 0.5'~5.0' DEM.In addition, taking the Nash coefficient, deterministic coefficient and relative error as the evaluation indicators of the simulation effect, it analyzes the variation trend of the number and relative errorof hydrological calculation units by the mean change point method, and discusses the optimal inflection point of the DEM scale effect. The results show that: (1) The resolution of DEM has a significant influence on the division of the number of hydrological calculation units, with the maximum number change rate of 98.13%; (2) The Nash coefficient, deterministic coefficient and relative error are less affected by the DEM resolution, with the change rate of 0.019%, 0.009% and 11.879% respectively in calibration period, and 0.009%, 0.012% and 9.552% respectively in verification period; (3) 1.0'DEM can significantly improve the operating efficiency of the model under the premise of guaranteeing the simulation accuracy, which is the optimal inflection point of DEM scale effect.